Perancangan User Interface Website Profil Perusahaan dengan menggunakan Metode Human Centered Design (HCD) dan Heuristic Evaluation (Studi Kasus: PT Mahitala Bramanta Digital) - Tara Rahmadilla Adhi; Satrio Hadi Wijoyo; Bondan Sapta Prakoso (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
PT Mahitala Bramanta Digital is an agency engaged in Information Technology Services that offers various digital solutions for company needs. However, the obstacles found by PT Mahitala Bramanta Digital are that there is no good company profile website user interface design that meets the company's and users' goals, and there is no user view of the website other than the company's internals. Based on the identification of the problems that occur, the researcher aims to produce a company profile website user interface design with a display that is able to meet the characteristics and philosophy of the company using the Human Centered Design (HCD) method. The HCD method is used to determine business processes and identify user use case diagrams in order to adapt to the needs and requirements of users and to suit the company's business goals. The evaluation used for the design of the solution uses the Heuristic Evaluation method which involves 3 evaluators. A total of 23 problems were found, then prioritized improvements were made to 12 problems that had an average severity rating of above 2. Repairs were also made to other problems based on the advice given by the evaluator and using the Usability Guidelines in the repair process so that it can be said that design solutions are in line with user reusability as well as company goals.